2004
DOI: 10.1016/s0014-5793(04)00425-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phalloidin and jasplakinolide on the flexibility and thermal stability of actin filaments

Abstract: In this work the effect of phalloidin and jasplakinolide on the dynamic properties and thermal stability of actin filaments was studied. Temperature dependent fluorescence resonance energy transfer measurements showed that filaments of Ca-actin became more rigid in the presence of phalloidin or jasplakinolide. Differential scanning calorimetric data implied that the stiffer filaments also had greater thermal stability in the presence of phalloidin or jasplakinolide. The fluorescence and calorimetric measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, the dynamic changes of the actin cytoskeleton in live sperm could not be followed unless actin was revealed by expressing fluorescent proteins together with the actin monomers. Most studies of F‐actin in sperm were performed using phalloidin, which is toxic and not capable of crossing the cell plasma membrane of live cells (Cooper, 1987; Vandekerckhove et al, 1985; Visegrády et al, 2004). These limitations impeded the use of this probe to study the actin cytoskeleton in real time using live cells.…”
Section: Dynamic Changes Of the Actin Cytoskeleton During The Armentioning
confidence: 99%
“…However, the dynamic changes of the actin cytoskeleton in live sperm could not be followed unless actin was revealed by expressing fluorescent proteins together with the actin monomers. Most studies of F‐actin in sperm were performed using phalloidin, which is toxic and not capable of crossing the cell plasma membrane of live cells (Cooper, 1987; Vandekerckhove et al, 1985; Visegrády et al, 2004). These limitations impeded the use of this probe to study the actin cytoskeleton in real time using live cells.…”
Section: Dynamic Changes Of the Actin Cytoskeleton During The Armentioning
confidence: 99%
“…Moreover, to preserve the thus assembled actin comets for AFM nano-indentation, phalloidin was used as a stabilizer to prevent actin filaments (F-actin) from disassembly. Previously, phalloidin has been shown to alter the mechanical properties of the actin filament (Isambert et al, 1995;Visegrády et al, 2004) probably due to a preserved structure closer to ATP-F-actin rather than ADP-F-actin (Ichetovkin et al, 2002). Since computational modeling showed that the status of ATP in F-actin determines its structure and hence its persistence length (Pfaendtner et al, 2009), instead of chemically altering the mechanical properties of the F-actin, it is more likely that phalloidin better preserves it.…”
Section: Phalloidin Stabilizationmentioning
confidence: 99%
“…Actinmodifying agents extracted from different sources such as cytochalasins, latrunculins, phalloidin, and jasplakinolide have been used extensively to elucidate microfilamentassociated functions (Mizuno et al 2002). Cytochalasins and latrunculins inhibit actin polymerization, whereas phalloidin and jasplakinolide both promote actin polymerization and stabilize polymerized actin, although with slightly different modes of action (Visegrády et al 2004;Bubb et al 1994;Cooper 1987). Cytochalasins compose a group of fungal metabolites, which permeates cell membrane and can cause ruffling and cells to round up (Shaw et al 2000).…”
Section: Introductionmentioning
confidence: 99%